Študij napršenih tankih plasti platine na polimerno podlago - Požun, Karol (Kovine zlitine tehnologije, 1999)
Pt thin film sputtered on plymer substrate forms the active structure of the relative humidity sensor. Due to exellent Pt electrical characteristics and corrosion resistivity it is of vital importance to throughly study the morphological properties of Pt. The propeties of Pt layer on polymer substrate were studied under different deposition conditions. The paper focuses on the morphological structure properties only. The structure properties of Pt films sputtered on polymer and KCl were studied by TEM. The film surface topography and diameter of the detected Pt islands were determined by AFM. The 10 and 20 nm thick Pt layers were deposited on the polymer substrate surface. The influence of substrate temperature on morphological properties was studied. The sample obtained on substrates at room temperature shows a discontinuous Pt layer structure with obvious cracks in it. The 20 nm thick Pt layer deposited on polymer result in nearly continuous polycrystalline film.
Keywords: polimeri; naprševanje; platina; relativna vlažnost; senzorji